Integrated management of tobacco caterpillar and cabbage butterfly with host plant resistant and organic amendment (Bangladesh Journal of Agricultural Research, 2018)
Field study was conducted at Patuakhali Science and Technology University, Patuakhali during 2013-2014 to know the effect of cabbage variety and organic agriculture on the damage potential of Spodoptera litura F. and Pieris brassicae L. Two cabbage varieties viz., Atlas-70 (V1) and Super tropic (V2), and organic agriculture like, M0 = control, M1 = cowdung @ 6 kgplot-1, M2 = mustard oilcake @ 750gplot-1, M3 = Vermicompost @ 3 kgplot-1 and M4 = Trichoderma @ 3 kgplot-1 were included in this study. Treatment combinations were V1M0, V1M1, V1M2, V1M3, V1M4, V2M0, V2M1, V2M2, V2M3 and V2M4. Results revealed that the lowest number of infested plants/plot and percent infested leavesplant-1 were found in variety Super tropic and trichoderma (V2M4) applied plots followed by variety Atlas-70 and vermicompost (V1M3) applied plots on different dates of observation while the highest number of infested plantsplot-1 and percent infested leaves plant-1 were in variety Super tropic and mustard oil cake (V2M2) applied plots followed by variety Atlas-70 and control (V1M0) applied plots. The highest number and percent (4.00 plot-1) and (20.00% plot-1) of infested heads were found in variety Super tropic and mustard oil cake (V2M2) applied plots followed by variety Atlas-70 and control plots (V1M0) (16.65%). The highest number of healthy heads plot-1 (19.67), healthy head yield (71.47 t ha-1) and total head yield (72.14 t ha-1) were recorded in variety Super tropic and Tricoderma (V2M4) applied plots followed by variety Atlas-70 and vermicompost (V1M3) (70.53 t ha-1) applied plots while the lowest number of healthy heads per plot, healthy head yield and total head yield were recorded in in variety Super tropic and mustard oil cake (V2M2) applied plots followed by variety Atlas-70 and control plots (V1M0).Bangladesh J. Agril. Res. 43(4): 619-630, December 2018